2021
DOI: 10.1108/ccsm-07-2020-0137
|View full text |Cite
|
Sign up to set email alerts
|

Moderating effects of national culture on the psychological contract breach and outcome relationship: a meta-analysis

Abstract: PurposeThis paper contains a meta-analysis of the psychological contract literature published in the last two decades. The aim of this paper was to investigate the moderating role of national culture in the individual-level relationships between psychological contract breach (PCB) and two important work outcomes, namely job performance (in-role and organizational citizenship behaviors) and turnover (actual and intended).Design/methodology/approachAfter an extensive literature search, 134 studies were found whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 130 publications
1
25
0
Order By: Relevance
“…Global managers could alternatively improve work relationships across different generations through mutual OCBs. In line with Jayaweera et al's (2021) suggestions, global managers should encourage employees to interact with one another and prioritize communication to help maintain effective informal work relationships. People are more likely to engage in OCBs where they help coworkers with whom they get along well and with whom they have quality relationships.…”
Section: Practical Implicationsmentioning
confidence: 95%
“…Global managers could alternatively improve work relationships across different generations through mutual OCBs. In line with Jayaweera et al's (2021) suggestions, global managers should encourage employees to interact with one another and prioritize communication to help maintain effective informal work relationships. People are more likely to engage in OCBs where they help coworkers with whom they get along well and with whom they have quality relationships.…”
Section: Practical Implicationsmentioning
confidence: 95%
“…Future orientation concerns the extent to which individuals engage in future-oriented behavior such as delaying gratification, planning, and investing in the future (House et al, 2004). In a society with high future orientation, individuals place more value on long-term rather than short-term results; they also tend to have stronger willingness to pursue goals to meet their future aspirations (Jayaweera et al, 2021).…”
Section: Normative Perspective Of Socioemotional Wealthmentioning
confidence: 99%
“…On the other hand, several empirical studies reported that breaching a psychological contract is one of the primary reasons influencing workers' performance (Amoah et al, 2021;Gulzar et al, 2021;Said et al, 2021). The breach of a psychological contract occurs when the fulfillment of one of the obligations interferes with a psychological contract between employer and employee, which leads to adverse consequences influencing satisfaction and mutual trust (Jayaweera et al, 2021). It also negatively affects the behavior of workers through continuous absenteeism and neglect of job duties, which may lead to increased employee turnover (Hammouri et al, 2015;Liu et al, 2020).…”
Section: Psychological Contract Fulfillmentmentioning
confidence: 99%